Engineering a growth sensor to select intracellular antibodies in the cytosol of mammalian cells - Nguyen, Thuy Duong; Takasuka, Hitoshi; Kaku, Yoshihiro; Inoue, Satoshi; Nagamune, Teruyuki; Kawahara, Masahiro (Journal of bioscience and bioengineering, 2017)
Intracellular antibodies (intrabodies) are expected to function as therapeutics as well as tools for elucidating in vivo function of proteins. In this study, we propose a novel intrabody selection method in the cytosol of mammalian cells by utilizing a growth signal, induced by the interaction of the target antigen and an scFv-c-kit growth sensor. Here, we challenge this method to select specific intrabodies against rabies virus nucleoprotein (RV-N) for the first time. As a result, we successfully select antigen-specific intrabodies from a naïve synthetic library using phage panning followed by our growth sensor-based intracellular selection method, demonstrating the feasibility of the method. Additionally, we succeed in improving the response of the growth sensor by re-engineering the linker region of its construction. Collectively, the described selection method utilizing a growth sensor may become a highly efficient platform for selection of functional intrabodies in the future.